Nate the Great and the Halloween hunt - Sharmat, Marjorie Weinman; Simont, Marc (New York : Yearling, 2005)
Nate and his trusty dog, Sludge, investigate when Rosamond's cat, Little Hex, turns up missing on Halloween night. Includes related facts, jokes, and activities.
"A Yearling book."
1.6
K-3
K-3.
370
Keywords: Nate the Great (Fictitious character) -- Fiction; Halloween -- Fiction; Mystery and detective stories; Nate the Great (Fictional character) -- Fiction; Halloween -- Fiction; Mystery fiction